Political Settings of Contemporary Moscow Youth - Sergeevna Novikova, Svetlana; Nikolaevich Mazaev, Yuriy; Olegovna Tokareva, Viktoriia; Evgenyevna Kiseleva, Evgeniia; Grigoryevna Kotovskaya, Mariya (Opción, 2019)
The article analyzes a range of political views and orientations of the Moscow youth based on the results of a sociological survey that was conducted by means of a poll. It was found out that young people of Moscow are predominantly characterized by an average interest in politics and the ruling elite orientation. At the same time, a considerable share of the capital’s young people is marked by an insufficiently high interest in politics, political views that run counter to the current power and an aspira- tion to take efforts to influence the elaboration and adoption of political decisions. A conclusion can be made that political settings of young people in Moscow are a contradictory, specific political and psychological pheno- menon that produces a substantial impact on the whole system of their political culture.